Pengaruh Dimensi Saluran Kemalir terhadap Perubahan Sifat Kimia Tanah dan Pertumbuhan Kedelai di Tanah Sulfat Masam - Muhammad Alwi; Dakhyar Nazemi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
The effect of different dimentions on field ditch to soil chemical changes under soybean planting at acid sulphate soil was being studied at wet season 2001. The experiment used split plot design with 3 replications. Inter field ditch spacing as a main plot consisted of 3, 6 and 9 m. Field ditch depth as a sub plot consisted of 20 and 40 cm. The result showed that space of field ditch 7.5 m and 20 cm of depth could improve soil chemical (pH, Al-dd, Fe-dd, SO, N, P), increased growth and yield of soybean.   Key words.. Field ditch, Soybean, Acid sulphate soil